2002
DOI: 10.1021/jp0135149
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Time-Resolved EPR Spectra of Systems Exhibiting Electron Spin Polarization Complicated by Magnetization Transfer

Abstract: In order that chemically induced dynamic electron polarization (CIDEP) can provide a means to explore dynamics in arbitrary systems such as inclusion compounds or sequential chemical reactions, the Bloch equations are extended for use with a system exhibiting electron spin polarization (ESP). Since CIDEP depends on time and external magnetic field and in this paper is observed by time-resolved electron paramagnetic resonance spectroscopy (TREPR), an algorithm for the general calculation of EPR signals that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The time developments of the computed quantities of ( M Z,1 + M Z, - 1 ) and ( M Z,1 − M Z, - 1 ) were convoluted with the response functions determined by the width (16 ns) of the π/2 microwave pulse . Several time-resolved EPR studies have suggested that homogeneous ET reactions between quinone anions and the dissolved neutral quinone molecules affect the decay time of the multiplet ( M Z,1 − M Z, - 1 ) contributions. ,, However, even if homogeneous ET were to occur, the effect needs not to be taken into account in this study, because both the net and the multiplet contributions were simulated with a common, single T 1 parameter in eq 3 as seen in Figure . These results indicate that the homogeneous ET rate is much slower than the original spin−lattice relaxation times of quinone anion radicals in the solvents used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The time developments of the computed quantities of ( M Z,1 + M Z, - 1 ) and ( M Z,1 − M Z, - 1 ) were convoluted with the response functions determined by the width (16 ns) of the π/2 microwave pulse . Several time-resolved EPR studies have suggested that homogeneous ET reactions between quinone anions and the dissolved neutral quinone molecules affect the decay time of the multiplet ( M Z,1 − M Z, - 1 ) contributions. ,, However, even if homogeneous ET were to occur, the effect needs not to be taken into account in this study, because both the net and the multiplet contributions were simulated with a common, single T 1 parameter in eq 3 as seen in Figure . These results indicate that the homogeneous ET rate is much slower than the original spin−lattice relaxation times of quinone anion radicals in the solvents used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The X-band TREPR measurements were carried out by using a magnet and console (Varian E-112) equipped with a microwave bridge (ER 041MR, Bruker, Billerica, MA) in which a microwave preamplifier was added to enhance the time resolution (Ϸ25 ns) and signal sensitivity (51). Light excitations were performed by using the second harmonic (532 nm) of a Nd:YAG laser (Spectra-Physics, Quanta-Ray GCR-4, full width at half maximum Ϸ 5 ns).…”
Section: Methodsmentioning
confidence: 99%
“…Another in-house program was used to simulate the spectra as sums of Gaussian curves. Chemically induced dynamic electron polarization (CIDEP) effects ,, were not taken into account by this program.…”
Section: Methodsmentioning
confidence: 99%